Antibacterial activities of and biofilm removal by Ablysin, an endogenous lysozyme-like protein originated from Acinetobacter baumannii 1656-2. (December 2020) - Kim, Shukho; Jin, Jong-Sook; Lee, Da-Won; Kim, Jungmin
Highlights: Ablysin is a novel peptidoglycan hydrolase identified in the genome of Acinetobacter baumannii . Ablysin has antimicrobial activity against A. baumannii, P. aeruginosa, E. coli, E. faecium, S. aureus and K. pneumoniae . Ablysin has a bactericidal effect on and biofilm-removing activity against A. baumannii . Ablysin represents a potential new class of antibacterial proteins for use to target MDR A. baumannii and other bacteria. Abstract: Objectives: Multidrug-resistant (MDR) Acinetobacter baumannii as well as MDR Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas aeruginosa and other Enterobacteriaceae ('ESKAPE' pathogens) currently present a major public-health problem. These bacteria are associated with opportunistic infections in intensive care units as well as in immunocompromised patients. There is an urgent need for new alternative antibacterials to control these MDR bacteria. Here we describe the antibacterial action of a novel peptidoglycan hydrolase that targets the bacterial cell wall, identified in the genome of clinical isolate A. baumannii 1656-2. Methods: We generated a recombinant protein from a sequence encoding a lysozyme-like protein identified in the genome of A. baumannii 1656-2. We named it Ablysin and tested its antibacterial activity and biofilm removal ability targeting ESKAPE pathogens. Results: In vitro application of Ablysin resulted in growth inhibition of the six aforementioned bacterial species, with a highest activity against A. baumannii . Electron microscopy revealed the concentration-dependent (250–2000 μg/mL) rupture of A. baumannii bacterial cells accompanied by elimination of the associated biofilm. Conclusions: Ablysin represents a potential new class of antibacterial proteins that can be used to target MDR A. baumannii as well as other bacterial species.